Bibliometric Analysis of Blockchain for E-Government: Historical Institutionalism and Governance of Secure Digital Identity in Public Sector Services - Dyah Kuntorini Dwi Angreni; Ana Zahara (Journal of Government and Politics (JGOP), 2026)
Blockchain has increasingly been discussed as a strategic technology for strengthening e-government, particularly in the development of secure digital identity systems. However, existing studies tend to emphasize technical benefits such as transparency, security, efficiency, and decentralization, while paying less attention to the institutional conditions that shape blockchain adoption in the public sector. This study aims to map the development of blockchain research in e-government and to interpret its implications for secure digital identity governance through the lens of Historical Institutionalism. The data were retrieved from on 20 June 2025 using keywords related to blockchain, e-government, public sector services, and digital identity. A total of 1,709 documents published between 2000 and 2025 were analyzed. Data collection was conducted through a structured bibliometric search strategy, followed by data cleaning, duplicate removal, and keyword standardization. The data were analyzed using VOSviewer to examine publication trends, keyword co-occurrence networks, thematic clusters, and the relationship among dominant research topics. The findings show a significant increase in publications after 2017, indicating the growing academic and policy attention to blockchain-based digital governance. The dominant themes are related to public services, government, health services, adoption challenges, regulation, cost, and data security. These findings suggest that blockchain adoption in e-government is not merely a technical issue, but also an institutional process shaped by regulatory readiness, administrative legacies, interoperability constraints, and public sector capacity. The theoretical contribution of this study lies in integrating bibliometric analysis with Historical Institutionalism, particularly the concepts of path dependence, critical juncture, institutional layering, and policy feedback. This study contributes to a more critical understanding of blockchain-based digital identity governance and offers implications for policymakers seeking to design secure, adaptive, and institutionally feasible digital public services.